The longitudinal association between depression, anxiety symptoms and HIV outcomes, and the modifying effect of alcohol dependence among ART clients with hazardous alcohol use in Vietnam. (24th June 2021) - Nguyen, Minh X; McNaughton Reyes, H. Luz; Pence, Brian W; Muessig, Kate; Hutton, Heidi E; Latkin, Carl A; Dowdy, David; Chander, Geetanjali; Lancaster, Kathryn E; Frangakis, Constantine; Sripaipan, Teerada; Ha Tran, Viet; et al.
Abstract: Introduction: Mental health disorders may negatively impact HIV outcomes, such as viral suppression (VS) and antiretroviral (ART) adherence among people with HIV (PWH) with hazardous alcohol use. This study evaluates the longitudinal association between depression, anxiety symptoms, VS and complete ART adherence among ART clients with hazardous alcohol use in Vietnam; and examines alcohol dependence as a modifier in this association. Methods: This was a secondary data analysis of a trial for hazardous drinking ART clients in Thai Nguyen, Vietnam. From March 2016 to May 2018, 440 ART clients with an Alcohol Use Disorders Identification Test‐Concise (AUDIT‐C) score ≥4 for men and ≥3 for women were enrolled. Individuals were randomized to either a combined intervention, a brief intervention or a standard of care. Data on sociodemographics, depression, anxiety symptoms, alcohol use, VS and ART adherence were collected at baseline, three, six, and twelve months. Generalized estimating equation models controlling for intervention exposure were used to estimate time‐lagged associations. Risk ratios were estimated using Poisson regression with robust variance estimation. Results: The mean age of participants was 40.2. The majority was male (96.8%), had at least some secondary school education (85.0%) and had a history of injection drug use (80.9%). No overall effect of depression and anxiety symptoms on VS was observed. When stratified by time, increased anxiety symptoms at six months were associated with VS at 12 months (adjusted risk ratio (aRR) = 1.09; 95% CI 1.02 to 1.17). An increase in depression or anxiety symptoms was associated with a decreased probability of complete ART adherence (depression symptoms: aRR = 0.95; 95% CI: 0.91 to 0.99; anxiety symptoms: aRR = 0.93; 85% CI: 0.88 to 0.99). The negative effects of anxiety symptoms on ART adherence were stronger among participants with alcohol dependence, compared to those without. Conclusions: Depression and anxiety symptoms had no overall effect on VS, although they were associated with a lower probability of complete ART adherence. Interventions focusing on mental healthcare for PWH with hazardous alcohol use are needed, and integration of mental healthcare and alcohol reduction should be implemented in HIV primary care settings.